Discovery of new species and country records for the North American sap beetle fauna (Coleoptera: Nitidulidae) - Cline, Andrew R.; Skelley, Paul E. (Zootaxa, 2013)
Brachypeplus habecki Cline and Skelley, sp. nov. is described from southern Texas, and Brachypeplus glaber LeConte is rediagnosed and discussed. Cyllodes thomasi Cline and Skelley, sp. nov. is described from southern Arizona, and Cyllodes biplagiatus is discussed. Habitus and genitalic photographs are provided as well as images of key diagnostic features for these species. An identification key is provided to distinguish the Brachypeplus and Cyllodes present in North America. Cryptarcha omisitoides Reitter, a previously unreported Central American nitidulid, is newly recorded from Arizona; and Carpophilus opthalmicus Murray, a previously unreported Caribbean species, is newly recorded from Florida. A discus-sion of Cryptarcha omisitoides and Carpophilus opthalmicus is also provided.